2016
DOI: 10.7589/2015-07-187
|View full text |Cite
|
Sign up to set email alerts
|

OCCURRENCE OF LUNGWORMS IN EUROPEAN WILDCATS (FELIS SILVESTRIS SILVESTRIS) OF CENTRAL ITALY

Abstract: The increasing focus on infections in domestic cats (Felis catus) has raised questions about lungworm distribution in wild hosts. To enhance knowledge of the occurrence of lungworms in enzootic regions of central Italy, we examined the carcasses of 16 European wildcats (Felis silvestris silvestris). Adult nematodes, feces, respiratory flushings, and pulmonary tissues were collected at necropsy and then microscopically and genetically analyzed. Fourteen wildcats had single or mixed lungworm species. Aelurostron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 46 publications
(65 reference statements)
2
74
0
Order By: Relevance
“…The European wild cats and domestic cats are two close relatives, which may live in sympatry, interbreed and even produce fertile offspring (Mattucci et al 2013). As a consequence of the close association between wild and domestic cats, both species may share pathogens and be at risk of the same infections (Veronesi et al 2016 b ). Thus, future studies should also include domestic cats from the areas where the wild cats positive for H. silvestris sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The European wild cats and domestic cats are two close relatives, which may live in sympatry, interbreed and even produce fertile offspring (Mattucci et al 2013). As a consequence of the close association between wild and domestic cats, both species may share pathogens and be at risk of the same infections (Veronesi et al 2016 b ). Thus, future studies should also include domestic cats from the areas where the wild cats positive for H. silvestris sp.…”
Section: Discussionmentioning
confidence: 99%
“…In Bosnia and Herzegovina, wild cats inhabit the northeastern part of the country, and areas along the northern and eastern border where they live in sympatry with domestic cats (Yamaguchi et al 2015). In the past few years, the interest of the scientific community in wild cats has increased as they have been recognized as natural reservoirs and potential source of pathogens for domestic cats (Falsone et al 2014; Gallusová et al 2016; Veronesi et al 2016 a , b ). …”
Section: Introductionmentioning
confidence: 99%
“…Wild animals such as the European wildcat (Felis silvestris silvestris), in which T brevior has been found, play a role as spreaders of the parasite in those areas where wildcats and domestic cats live in sympatry. 5,29,30 indeed, T brevior has been mostly described thus far in cats living in areas of italy and Greece where wildcat populations are present. 2,5,30,31 Additionally, in domestic cats, T brevior is often found in association with A abstrusus.…”
Section: T Breviormentioning
confidence: 99%
“…5,29,30 indeed, T brevior has been mostly described thus far in cats living in areas of italy and Greece where wildcat populations are present. 2,5,30,31 Additionally, in domestic cats, T brevior is often found in association with A abstrusus. 22,[25][26][27] A recent retrospective study demonstrated negligible occurrence of Troglostrongylus species in domestic cats living in subApennine territories of central italy during the years 2002-2013.…”
Section: T Breviormentioning
confidence: 99%
“…The role of parasites in wildlife population decline is not well documented. However, parasites occurrence, mode of infection and possible impacts in wildlife are documented, mostly using samples from dead animals and from zoo samples (Polley 2005, Zhang et al 2008, Bertelsen et al 2010, De Craeye et al 2011, Veronesi et al 2016. In Nepal, only few baseline surveys on wildlife are documented so far on parasite prevalence and interaction with livestock.…”
Section: Introductionmentioning
confidence: 99%